Corporate Governance Structure Impact on Bank Firm Value in Indonesia 2021-2024 - Meyta Ayu Resandy; Marsono Marsono (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2025)
National economic stability is influenced by the banking sector as a financial intermediary. This study develops an agency theory based model to explain the role of corporate governance in enhancing firm value. Using quantitative methods with multiple linear regression, the research examines banking companies listed on the Indonesia Stock Exchange (IDX) during 2021 to 2024, based on secondary data from annual reports. Analysis includes classical assumption tests and hypothesis testing. Results show that corporate governance structures such as board size, audit committee size, board independence, and institutional ownership significantly affect firm value (Tobin’s Q). Board size, audit committee size, and board independence have positive effects, while institutional ownership has a negative effect. The findings contribute to strengthening corporate governance practices in the Indonesian banking sector.